Structural Characterization and Anti-inflammatory Activities of Anticomplementary Polysaccharides from Rhododendron principis - Zhao, Zhi-Zhi; Zhang, Jie; Hong, Zhou; Bao, Wei-Lian; Zhou, Li-Shuang; Liu, Yang; De-ji; Chen, Dao-Feng; Lu, Yan (Planta Medica, 2023)
Rhododendron principis leaves have been used as “Dama”, a Traditional Tibetan Medicine for treating inflammatory diseases. R. principis crude polysaccharides with anticomplementary activity demonstrated promising anti-inflammatory effects on acute lung injury induced by lipopolysaccharide. R. principis crude polysaccharides significantly decreased the levels of TNF-α and interleukin-6 in both serum and blood and bronchoalveolar lavage fluid in lipopolysaccharide-induced acute lung injury mice by intragastric administration (100 mg/kg). A heteropolysaccharide, ZNDHP, was obtained from R. principis crude polysaccharides with successive anticomplementary activity-guided separation. ZNDHP was characterized as a branched neutral polysaccharide with a backbone composed of → 2)-β-Glcp-(1→, → 2,6)-α-Glcp-(1→, → 6,3)-β-Galp-(1→, → 2,6)-α-Galp-(1→, → 6,2)-β-Glcp-(1→, → 4)-α-Glcp-(1→, → 5)-β-Araf-(1→, → 3,5)-α-Araf-(1→, and → 4,6)-β-Manp-(1→, and the backbone structure was further confirmed by partial acid hydrolysis. In addition to anticomplementary and antioxidant activities, ZNDHP exhibited potent anti-inflammatory activity by significantly inhibiting the secretion of nitric oxide, TNF-α, interleukin-6, and interleukin-1β of lipopolysaccharide-treated RAW 264.7 cells. However, all of these activities decreased greatly after partially hydrolyzing, indicating the importance of the multibranched structure for its bioactivity. Therefore, ZNDHP might be an important component of R. principis for treating inflammation.
Keywords: Ericaceae; Rhododendron principis; polysaccharide; anti-inflammatory; anticomplementary; structure characterization